Pasireotide for acromegaly: long-term outcomes from an extension to the Phase III PAOLA study. Issue 6 (June 2020) - Colao, Annamaria; Bronstein, Marcello D; Brue, Thierry; De Marinis, Laura; Fleseriu, Maria; Guitelman, Mirtha; Raverot, Gerald; Shimon, Ilan; Fleck, Jürgen; Gupta, Pritam; Pedroncelli, Alberto M; Gadelha, Mônica R
Abstract : Objective: In the Phase III PAOLA study (clinicaltrials.gov: NCT01137682), enrolled patients had uncontrolled acromegaly despite ≥6 months of octreotide/lanreotide treatment before study start. More patients achieved biochemical control with long-acting pasireotide versus continued treatment with octreotide/lanreotide (active control) at month 6. The current work assessed the extent of comorbidities at baseline and outcomes during a long-term extension. Design/methods: Patients receiving pasireotide 40 or 60 mg at core study end could continue on the same dose in an extension phase if biochemically controlled or receive pasireotide 60 mg if uncontrolled. Uncontrolled patients on active control were switched to pasireotide 40 mg, with the dose increased at week 16 of the extension if still uncontrolled (crossover group). Efficacy and safety are reported to 304 weeks (~5.8 years) for patients randomized to pasireotide (core + extension), and 268 weeks for patients in the crossover group (extension only). Results: Almost half (49.5%; 98/198) of patients had ≥3 comorbidities at core baseline. During the extension, 173 patients received pasireotide. Pasireotide effectively and consistently reduced GH and IGF-I levels for up to 5.8 years' treatment; 37.0% of patients achieved GH <1.0 µg/L and normal IGF-I at some point during the core or extension. Improvements were observed in key symptoms. The long-term safety profile was similar to that in the core study; 23/173 patients discontinued treatment because of adverse events. Conclusions: In this patient population with a high burden of comorbid illness, pasireotide was well tolerated and efficacious, providing prolonged maintenance of biochemical control and improving symptoms.